Investigating curricular policy as a tool to dismantle the master's house: Indian Education for All and social studies teacher education. Issue 6 (September 2018) - Stanton, Christine R; Morrison, Danielle
US curricular policies frequently bolster neoliberal power structures within both pre-K to 12 schools and universities by privileging settler–colonial narratives and excluding Indigenous knowledge. However, curricular policies can also serve to enhance social reconstructionist and social justice education. In this article, we describe two case studies focused on a state-level policy—Montana's Indian Education for All—aimed at advancing understandings about Indigenous experiences and worldviews. The first study's findings demonstrate Indian Education for All's potential to support practicing teachers, including teachers with limited experience working with Indigenous communities, in their efforts to confront settler-colonialism and neoliberalism within curricula. The results from our second study suggest the potential for Indian Education for All to create space for Indigenous student leadership. However, our research also provides cautionary notes about the potential for "tools, " such as Indian Education for All, to unintentionally reinforce settler-colonialism, neoliberalism, and racism, as they can create opportunities for racial microaggressions and inequitable expectations. We conclude with recommendations for teacher education programs, institutional leaders, and policymakers.